Pulmonary manifestations of chronic HPV infection in patients with recurrent respiratory papillomatosis. Issue 10 (October 2022) - Pai, Sara I; Wasserman, Isaac; Ji, Yisi D; Gilman, Matthew; Hung, Yin P; Faquin, William C; Mino-Kenudson, Mari; Muniappan, Ashok
Summary: Human papillomavirus (HPV) types 6 and 11 can infect the squamous epithelium of the respiratory tract. Up to 8·9% of patients with HPV-associated recurrent respiratory papillomatosis (RRP) have pulmonary involvement. Pulmonary manifestations of HPV infection are associated with considerable morbidity, in part because treatment options and management guidelines are lacking. Patients with pulmonary RRP have a 32-times increased lifetime risk of malignant transformation compared with the overall RRP population. We review the clinical and radiographic presentation, pathological features, and genetics of pulmonary RRP, and we provide management algorithms based on our clinical experience with this complex patient population. In patients with suspected pulmonary involvement, tissue-sparing procedures to address growing lesions might be warranted given the chronicity and multifocality of the disease over a patient's lifetime. However, malignant transformation of pulmonary lesion(s) warrants standard-of-care treatment for primary lung squamous cell carcinoma. Large cohort studies are needed to understand the clinical course of pulmonary RRP and to identify molecular markers of increased risk of malignant transformation in order to develop guidelines for optimal and standardised surveillance and treatment.